Consumer Brand-Relationship and Privacy Concerns to Repurchase Intention in Online Shopping Application - Nadia Anggraini Putri; Ira Fachira (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study examines how the consumer relationship with a brand on repurchase intention after their data are leaked through online and able to be accessed by many people. This paper is proposing to analyze the concept of consumer brand-relationship about the consumer trust and consumer satisfaction and analyze the effect after consumer privacy concern towards their intention to repurchase it in the same online shopping application. This research was conducted using a PLS-SEM. The results finds that trust has no impact towards repurchase intention because the findings of its consumer have already lost their trust and put their concern about their privacy about their data first before do the repurchase intention in a brand and the others are have impact towards the purchase intention.